Comparison of Purity and Concentration Values of Mycobacterium tuberculosis DNA Extraction Result from the Boiling and Spin Column Method - Febriyanti, Intan; Djuminar, Ai; Merdekawati, Fusvita; Indra , Asep Iin Nur (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2023)
The Polymerase Chain Reaction (PCR) technique is extensively employed in molecular biology to precisely detect Mycobacterium tuberculosis. Prior to conducting PCR, extracting of high-quality genomic Deoxyribonucleic Acid (DNA) is crucial to ensure accurate and reliable results. The primary objective of this study is to conduct a comparative analysis of the purity and concentration of M. tuberculosis DNA acquired through the utilization of the boiling method and the spin column extraction methods. A descriptive comparative research design was employed, utilizing a sample of 16 sputum specimens that had previously been confirmed as positive for M. tuberculosis through Acid-Fast Bacteria (AFB) examination and Molecular Rapid Test (MRT). The extraction of DNA was carried out using the boiling method and the spin column method. Subsequently, the concentration and purity of the extracted DNA were assessed using the NanoDrop Spectrophotometer, and the results were compared. The obtained yield of M. tuberculosis DNA isolates through the boiling method ranged from 9.6 ng/µL to 1258.7 ng/µL, with an average purity value of 1.23. Conversely, for the spin column method, the concentration of M. tuberculosis DNA isolates ranged from 8.7 ng/µL to 207.8 ng/µL, with an average purity value of 1.83. In conclusion, there is a significant difference between the purity and concentration of M. tuberculosis DNA extraction results using the boiling method and spin column methods.